2018
DOI: 10.3389/fnhum.2018.00157
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Prefrontal-Amygdala Pathway, Self-Reported Emotion, and Erection in Psychogenic Erectile Dysfunction Patients With Normal Nocturnal Erection

Abstract: Background: Neuroimaging studies have demonstrated that the prefrontal cortex and amygdala play an important role in sexual arousal (SA). However, little is known about the interactions between the prefrontal and cortex amygdala, which mediate the cognitive regulation of emotion and SA.Objective: We seek to determine whether nocturnal erection of psychogenic erectile dysfunction (pED) patients are normal and whether there are changes of topological organization in the prefrontal-amygdala pathway of brain netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…AE patients with psychogenic factors are characterized by a preserved genital reaction but a decreased subjective reaction (Waldinger & Schweitzer, ). The processes of erection and ejaculation are found to be related with both peripheral neural pathways and cerebral neural system (Clement & Giuliano, ; Chen et al ., ,b,c; Priviero et al ., ). The results of our previous studies showed that psychological factors were correlated with the pathophysiology of psychogenic erectile dysfunction, which is considered as a ‘brain disorder’ with impaired sexual arousal, cognitive, and affective processing in the brain (Chen et al ., , 2018a, 2018b, 2018c).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…AE patients with psychogenic factors are characterized by a preserved genital reaction but a decreased subjective reaction (Waldinger & Schweitzer, ). The processes of erection and ejaculation are found to be related with both peripheral neural pathways and cerebral neural system (Clement & Giuliano, ; Chen et al ., ,b,c; Priviero et al ., ). The results of our previous studies showed that psychological factors were correlated with the pathophysiology of psychogenic erectile dysfunction, which is considered as a ‘brain disorder’ with impaired sexual arousal, cognitive, and affective processing in the brain (Chen et al ., , 2018a, 2018b, 2018c).…”
Section: Introductionmentioning
confidence: 97%
“…The processes of erection and ejaculation are found to be related with both peripheral neural pathways and cerebral neural system (Clement & Giuliano, ; Chen et al ., ,b,c; Priviero et al ., ). The results of our previous studies showed that psychological factors were correlated with the pathophysiology of psychogenic erectile dysfunction, which is considered as a ‘brain disorder’ with impaired sexual arousal, cognitive, and affective processing in the brain (Chen et al ., , 2018a, 2018b, 2018c). Moreover, many brain structures are involved in the sexual response, such as the pre‐frontal cortex, parietal lobe, cingulate gyrus, amygdala, thalamic, and hypothalamic (Ruesink & Georgiadis, ; Georgiadis & Kringelbach, ).…”
Section: Introductionmentioning
confidence: 99%
“…30 Chen et al investigated psychogenic components of ED and determined that amygdala abnormalities could be a factor. 31 Although the aforementioned studies primarily focused on neuropharmacologic advancement, their findings provided a rationale for addressing auricular-acupuncture projections of the amygdala as part of protocols for patients with ED who desire this treatment. In a 2007 article, Soliman proposed auricular therapy for somatotopic projection of the amygdala in the Phase 3 zone (in addition to various other projections).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…There are many studies on the brain MRI of psychogenic ED [7,[19][20][21][22][23][24][25][26][27][28][29][30][31]. Despite significant progress, the mechanism aiming at CNS targets treated by tadalafil is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Normal erectile function is a result of the harmonious regulation and control of the central nervous system (CNS), which includes the supraspinal centres, the spinal cord and peripheral nerves. In the last two decades, exploring the role of CNS in sexual arousal by functional and structural neuroimaging studies, the magnetic resonance imaging (MRI) [20] such as diffusion tensor imaging (DTI) [21,[23][24][25], functional MRI (fMRI) and resting-state fMRI attracted many researchers [23][24][25]. Since 2002, compared with healthy subjects (HS), much researchers have found that psychologic ED patients showed significant changes in cerebral functions.…”
Section: Introductionmentioning
confidence: 99%